The Influence of Insurance Status on the Surgical Treatment of Acute Spinal Fractures. Issue 1 (January 2016) - Daly, Michael C.; Patel, Madhukar S.; Bhatia, Nitin N.; Bederman, S. Samuel
Abstract : Study Design: A retrospective, propensity score, multivariate analysis of the National Trauma Data Bank (NTDB) between 2008 and2011. Objective: The aim of this study was to determine the relationship between insurance status and rates of surgery for acute spinal fractures with and without spinal cord injury (SCI). Summary of Background Data: The decision for surgery in patients with spinal fractures is often based on fracture pattern and stability, associated SCI, and the presence of ligamentous and other associated injuries. It is poorly understood how nonclinical factors, such as insurance status, influence the decision for surgical intervention in patients sustaining spinal trauma. Methods: Using NTDB admission years 2008 to 2011, we included patients 18 to 64 years old who sustained a fracture of the cervical or thoracolumbar spine. Patients were excluded if they sustained polytrauma (Injury Severity Score ≥27) or a major injury (Abbreviated Injury Scale severity ≥3) to the head, thorax, or abdomen. Our main outcome measure was surgical versus nonsurgical treatment for spinal injury; our main predictor was insurance status. Hierarchical multivariate regression analysis and propensity scores were used to determine the relationship between insurance status and surgical treatment, controlling for other factors. We calculated adjusted odds ratios (ORs) for rates of surgery. Results: Our propensity score multivariate analysis demonstrated significantly higher rates of surgery in patients with SCI (OR = 11.76, P < 0.001), insurance (OR = 1.27, P < 0.001), white (OR = 1.21, P = 0.018) versus black race, blunt trauma (OR = 5.63, P < 0.001), shock (OR = 1.62, P < 0.001), higher Glasgow Coma Scale (GCS) score (OR = 1.02, P = 0.002), transfer from lower acuity hospital (OR = 1.51, P < 0.001), and treatment at teaching hospitals (OR = 1.49, P < 0.001). Multivariable subgroup analysis of SCI patients similarly revealed higher surgical rates for insured patients (OR = 1.46, P < 0.001) than those without insurance. Conclusion: Patients with traumatic spine fractures were more likely to receive surgery if they were insured, regardless of the presence of SCI. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text